Development of Clostridium tyrobutyricum as a Microbial Cell Factory for the Production of Fuel and Chemical Intermediates From Lignocellulosic Feedstocks - Linger, Jeffrey G.; Ford, Leah R.; Ramnath, Kavita; Guarnieri, Michael T. (Frontiers in Energy Research, 2020)
Microbial conversion of renewable, lignocellulosic substrates to fuel and platform chemical intermediates offers a sustainable route to establish a viable bioeconomy. However, such approaches face a series of key technical, economic, and sustainability hurdles, including: incomplete substrate utilization, lignocellulosic hydrolysate and/or end-product toxicity, inefficient product recovery, incompatible cultivation requirements, and insufficient productivity metrics. Development of a production host with native traits suitable for high productivity conversion of lignocellulosic substrates under process-relevant conditions offers a means to bypass the above-described hurdles and accelerate the development of microbial biocatalyst deployment. Clostridium tyrobutyricum, a native producer of short chain fatty acids, displays a series of characteristics that make it an ideal candidate for conversion of lignocellulosic substrates and thus represents a promising host for microbial production of diverse carboxylate-derived product suites. Herein, we review recent progress and future directions in the development of this bacterium as an industrial microbial cell factory, with emphases on the utilization of lignocellulosic substrates and metabolic engineering approaches.